Evaluation of Moringa (Moringa oleifera Lamp) powders and seed aqueous extract for the control of Khapra Beetle (Trogoderma granarium Everts) - Mohammed, Dr. Ashwag Ahmed; kheir, Dr Seif Eldin Mohamed; Ismeal, Elhadi Musa (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study investigated the comparative efficacy of Moringa ( Moringa oleifera Lamp) powdersfrom different plant parts (leaf, flower, seed and branch) on the suppression of khapra beetle(Trogoderma granarium (Everts.) (the 3rdlarval instar) damage in sorghum grains. Three rates 1%,2.5%, and 5% w/w of the plant powders were used under laboratory conditions. The experiment waslaid out in Completely Randomized Design (CRD) of four treatments. Each treatment was replicatedfour times .Ten larvae of khapra beetle were introduced into each petridish . Mortality of khaprabeetle larvae was recorded after 1, 3, 7 and 30 days. Result indicated that Moringa seeds powderwas more effective in causing khapra beetle larvae mortality. The sorghum grains treated withMoringa seed powder gave a high range of 7.5- 2.5% larvae mortality compared to the low range of2.5- 0.0% recorded in sorghum grains treated with Moringa leaves powder at 1 day. A progressiveincrease in mortality ranging from 15.0-42.5% in sorghum grains treated with Moringa seed powderand 12.5- 22.5% sorghum grains treated with Moringa leaves powder were achieved at 5% rate after3 and 30 days respectively. The LC50 and LC90 revealed that Moringa seed powder to be the mosteffective one. Also result revealed that Moringa seed powder is more effective than seed aqueousextract in the control of khapra beetle larvae. Out of the four powder parts of the Moringainvestigated , seed powder was the most effective biopesticide and thus will be recommended